Routledge handbook of nature and environmental aesthetics
1 online resource
Keywords: This handbook provides the first comprehensive overview of philosophical thinking about the aesthetics of the natural and human-made environments, exploring the topic's foundations, key ideas, and current debates.Throughout history and across cultures, people's perceptions of beauty and ugliness in their surroundings have been an important part of the human experience. This volume contains more than 30 contributions from leading scholars examining environmental appreciation from a variety of perspectives. Chapters cover a wide range of environments and issues, including the aesthetics of animals, natural sounds, gardens, the urban environment, and the relation between aesthetics and environmentalism. It also explores new topics such as the appreciation of nature in ancient thought, love of place, the traditional nature aesthetics of China and Japan, and the aesthetics of climate change.The Routledge Handbook of Nature and Environmental Aesthetics will be essential reading for students and scholars working on the aesthetics of environment, as well as anyone who wants to think deeply about environmental beauty. Scholars working in related fields outside academic philosophy, such as geography, landscape studies, environmental psychology, and environmental studies will also find it an invaluable guide to contemporary debates.